LIMITED LIABILITY AND ADDITIONAL LIABILITY COMPANY - AS A SUBJECT OF CIVIL LAW - Khushbakova Nigora Gayrat qizi (Scholar Express Journals, 2023)
This article describes in detail the legal status of the limited and additional liability company, the rights and duties of its participants, the regulation of its activities by law and other legal documents, the formation of the chartered fund of the LLC and the internal audit service
Keywords: Limited liability company; additional liability company; chartered fund